An integrated aerobic-anaerobic strategy for performance enhancement of Pseudomonas aeruginosa-inoculated microbial fuel cell. (October 2017) - Yong, Xiao-Yu; Yan, Zhi-Ying; Shen, Hai-Bo; Zhou, Jun; Wu, Xia-Yuan; Zhang, Li-Juan; Zheng, Tao; Jiang, Min; Wei, Ping; Jia, Hong-Hua; Yong, Yang-Chun
Graphical abstract: Highlights: Aerobic start-up improved the electron shuttle production of P. aeruginosa . The two-stage procedure promoted biofilm formation on the anode surface. Integrated aerobic-anaerobic strategy is practical to enhance MFC performance. Abstract: Microbial fuel cell (MFC) is a promising device for energy generation and organic waste treatment simultaneously by electrochemically active bacteria (EAB). In this study, an integrated aerobic-anaerobic strategy was developed to improve the performance of P. aeruginosa -inoculated MFC. With an aerobic start-up and following an anaerobic discharge process, the current density of MFC reached a maximum of 99.80 µA/cm 2, which was 91.6% higher than the MFC with conventional constant-anaerobic operation. Cyclic voltammetry and HPLC analysis showed that aerobic start-up significantly increased electron shuttle (pyocyanin) production (76% higher than the constant-anaerobic MFC). Additionally, enhanced anode biofilm formation was also observed in the integrated aerobic-anaerobic MFC. The increased pyocyanin production and biofilm formation promoted extracellular electron transfer from EAB to the anode and were the underlying mechanism for the MFC performance enhancement. This work demonstrated the integrated aerobic-anaerobic strategy would be a practical strategy to enhance the electricity generation of MFC.